2016
DOI: 10.1590/0047-2085000000128
|View full text |Cite
|
Sign up to set email alerts
|

Imagem corporal de gestantes: um estudo longitudinal

Abstract: RESUMO Objetivos Comparar atitudes corporais, atitudes alimentares, sintomas depressivos, autoestima, ansiedade e índice de massa corporal (IMC) de gestantes em diferentes momentos ao longo da gestação, bem como verificar a influência que as variáveis estudadas exercem sobre as atitudes corporais no primeiro, segundo e terceiro trimestre gestacional. Métodos Foram incluídas 17 gestantes que frequentavam o exame pré-natal na cidade de Juiz de Fora-MG, entre 22 e 41 anos de idade (média de 30,76 ± 5,65 anos)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
0
7
0
12
Order By: Relevance
“…The results of the regression analyses pointed out that eating attitudes and self-esteem were predictors of the body attitudes of pregnant women in both groups. Previous studies had already demonstrated the influence of eating attitudes 8,9 and self-esteem 6 in the body image of pregnant women. Nonetheless, in this study, the percentage that explains these variables on the BAQ was different according to the sector.…”
Section: Tablementioning
confidence: 97%
See 2 more Smart Citations
“…The results of the regression analyses pointed out that eating attitudes and self-esteem were predictors of the body attitudes of pregnant women in both groups. Previous studies had already demonstrated the influence of eating attitudes 8,9 and self-esteem 6 in the body image of pregnant women. Nonetheless, in this study, the percentage that explains these variables on the BAQ was different according to the sector.…”
Section: Tablementioning
confidence: 97%
“…Moreover, external and internal structures may impact on the mental health of these women. 2,8 Consequently, it is important to pay attention to the pregnant women of the public sector in order to prevent emotional disturbances during this period of their lives. Regarding the anthropometric variables, a significant difference was observed regarding the age and BMI of pregnant women in both evaluated groups.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…e em risco de depressão pós-parto, 1 desconsiderando que no período gravídico possam surgir outros agravos que comprometam a saúde mental e a vivência da maternidade. 33 Sui, Turnbull & Dodd 34 identificaram variações nos níveis de autoestima entre gestantes de acordo com a paridade. Multíparas apresentavam maior insatisfação corporal que primíparas, e a justificativa seria o maior ganho de peso gestacional e IMC.…”
Section: Eu Tenho Preocupação Sim De Como Vai Ficar O Meu Corpo [unclassified
“…Também é nesse período que ocorrem mais queixas físicas, já que as transformações do corpo limitam a realização de atividades cotidianas; por isso, devem ser abordadas e monitoradas durante a assistência prénatal e puerpério. 33,36 Neste estudo, todas as entrevistadas se encontravam no período gravídico, e foram identificadas três referências aos agravos à saúde e incômodos relacionados ao ganho de peso excessivo e alteração das formas corporais: No relato abaixo, foi possível observar a aceitação do ganho de peso excessivo. De acordo com Meireles et al, 37 o período gravídico promove um estado de tolerância ao aumento da gordura corporal por algumas mulheres, expresso pelo uso dos termos "bom", "tranquilo" e "desencanada".…”
Section: Limitações Físicas E Expectativas No Pós-partounclassified